Entropy analysis for ethylene glycol hybrid nanofluid flow with elastic deformation, radiation, non-uniform heat generation/absorption, and inclined Lorentz force effects - Unyong, B.; Vadivel, R.; Govindaraju, M.; Anbuvithya, R.; Gunasekaran, Nallappan (Case studies in thermal engineering, 2022)
Impact of non-uniform heat source/sink and elastic deformation on entropy generation analysis for Cu − Fe3O4/ethylene glycol hybrid nanofluid flow past a stretching sheet with an inclined magnetic field, partial slip, and thermal radiations are investigated. Appropriate conversions are utilized for PDE's into ODE's. The dimensionless form is then analytically solved with the help of a hypergeometric function. Performance of significant variables on the hybrid nanofluid flow, heat distribution, skin friction coefficient, Nusselt number, and entropy generation are obtained and discussed with the help of different graphs. Some main results reported in this article reveals that the presents of hybrid nanoparticle, partial slip, inclined magnetic field, and Eckert number improve the more heat conduction in Cu − Fe3O4/ethylene glycol hybrid nanofluid and Partial slip, non-uniform heat source, and Eckert numbers are minimized the entropy production. Skin friction coefficient improves through higher values of Cupper nanoparticles and suction parameter. Heat transfer rate is more for higher values of Cupper nanoparticles, non-uniform heat source, partial slip, thermal radiation, and Eckert number.